APPLICATION OF MULTIFACTOR DISPERSION ANALYSIS WITH THE PURPOSE OF QUALITATIVE ASSESSMENT OF THE INFLUENCE OF FACTORS ON THE SENSITIVITY OF THE CAPACITIVE HUMIDITY SENSOR - KRYLIK, Lyudmila (Herald of Khmelnytskyi National University. Technical sciences, 2022)
In order to qualitatively assess the influence of such factors as the thickness of the moisture-sensitive layer, the concentration of the NaCl salt solution as an adsorbing material and their combined effect on the sensitivity of the capacitive humidity sensor, a multivariate dispersion analysis was used. Capacitive humidity sensors served as experimental samples. Capacitive humidity sensors are made on a 0.7×0.9 mm sitall substrate. A copper film is applied to the surface of the sitall substrate, which forms the covers of the capacitive humidity sensors in the form of a meander with the appropriate geometry of 7.85·10-2×150·10-6×1.2·10-6 m. In such a design, the moisture-sensitive layer is hygroscopic salt, which serves as a dielectric. To create a moisture-sensitive film, solutions of hygroscopic salt NaCl with concentrations of 0.89 mol/l and 5.33 mol/l were used. They were applied to the surface of capacitive humidity sensors with a spray gun at a distance of 40-50 cm with thicknesses of 5.0 μm and 10.0 μm. A multifactor plan was developed in the case of two qualitative factors. The research results were obtained on the basis of the comparison of the factor variance, which is due to the influence of the factor, and the residual variance, which is due to the influence of random causes. Factorial and residual variance were compared using the value of Fisher's test. Using multivariate dispersion analysis, it was found that the concentration of the NaCl salt solution has a significant influence on the response of the model, namely the sensitivity of the capacitive humidity sensor. In this case, the value of Fisher's criterion observed in the experiment significantly exceeds the critical value of Fisher's criterion, namely 22.77>4.75 (F>Fck). The influence of such factors as the thickness of the moisture-sensitive layer and the combined effect of the thickness of the moisture-sensitive layer and the concentration of the salt solution is insignificant, i.e. the difference in the response values ​​of the model is related to its random nature rather than to the change in the value of the factor. Using the dispersion analysis of the influence of the factor, it was proved that regardless of the design of the capacitive humidity sensors, the concentration of the salt solution used to create the moisture-sensitive layer significantly affects the sensitivity of the capacitive humidity sensor.
Keywords: multivariate variance analysis; factor; model response; Fisher criterion; sensitivity; capacitive humidity sensor